2017
DOI: 10.3382/ps/pex114
|View full text |Cite
|
Sign up to set email alerts
|

The sub-inhibitory theory for antibiotic growth promoters

Abstract: Antibiotics have played a critical role in the prevention, control, and treatment of bacterial diseases in humans and animals, and as growth promoters (AGPs) when used at sub-therapeutic concentrations in animal production. Numerous hypotheses have been proposed for the effectiveness of AGPs, which have largely centered on the beneficial modulation of the intestinal microbiota. However, these hypotheses have been doubted by some researchers, as AGPs are fed at concentrations that would typically be below minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 32 publications
2
60
0
6
Order By: Relevance
“…It is further hypothesized that the growth promoting effect is based on inflammation-restricting characteristics of the AGP ( Niewold, 2007 ). Although an anti-inflammatory activity of various AGP is corroborated by several authors ( Kroismayr et al, 2008 ; Khadem et al, 2014 ; Palamidi et al, 2016 ), the opinions still differ regarding their real mode of action ( Broom, 2017 ). Because there is evidence of anti-inflammatory activity of several macrolides (e.g., tylvalosin, tilmicosin, and TYL) on immune cells ( Cao et al, 2006 ; Buret, 2010 ; Zhao et al, 2014 ), we included the APG TYL in tests on NF-κB and the inflammatory target genes.…”
Section: Discussionmentioning
confidence: 95%
“…It is further hypothesized that the growth promoting effect is based on inflammation-restricting characteristics of the AGP ( Niewold, 2007 ). Although an anti-inflammatory activity of various AGP is corroborated by several authors ( Kroismayr et al, 2008 ; Khadem et al, 2014 ; Palamidi et al, 2016 ), the opinions still differ regarding their real mode of action ( Broom, 2017 ). Because there is evidence of anti-inflammatory activity of several macrolides (e.g., tylvalosin, tilmicosin, and TYL) on immune cells ( Cao et al, 2006 ; Buret, 2010 ; Zhao et al, 2014 ), we included the APG TYL in tests on NF-κB and the inflammatory target genes.…”
Section: Discussionmentioning
confidence: 95%
“…Lee et al (2012) reported that feeding antimicrobials (decoquinate and monensin) to broiler chicks between 1 and 43 DOA altered the percentages of MHCII+ and CD4+ intestinal intraepithelial lymphocytes and their expression of various cytokines and chemokines compared with untreated controls. While direct effects of antimicrobials on gut immune-related cells, even at sub-therapeutic concentrations, is possible (Niewold, 2007), it is more likely that these effects are mediated through changes to the intestinal microbiome (Broom, 2017).…”
Section: Important Factors That Can Influence the Development Of The mentioning
confidence: 99%
“…The advantages of using antibiotics as growth promoters have been extensively studied and reviewed ( Jones and Ricke, 2003 ; Dibner and Richards, 2005 ). Although the exact mechanism of action still needs to be elucidated, the administration of subtherapeutic doses of antibiotics in chickens' diet is believed to alter the intestinal microbiota to improve feed efficiency ( Broom, 2017 ). Because various antibiotics will have different effects on the bacterial membership in the ceca ( Costa et al., 2017 ), the exact microbiota composition that leads to increased performances with the use of antibiotic growth promoters is still unclear.…”
Section: Discussionmentioning
confidence: 99%